Kedudukan Hukum Baitul Mal Wat Tamwil (BMT) Sebagai Lembaga Keuangan Bukan Bank Dengan System Syariah - Atin Meriati Isnaini (Jatiswara, 2016)
Indonesia as a State law and State unity that holds the principle culturally diverse that were in fact very diverse religious, ethnic, racial and cultural but Indonesia as a unitary state which berasaskan Pancasila which hold tight and fast to the precepts contained in the Pancasila that one of them is deity maha esa enshrined in the teachings of the religion freely without any act of interference from other religions and coercion by the lainuntuk realizing one of the teachings of Islam are shaped muamalah in Indonesia, the more the growth of Islamic banking and even various kinds of institutions of sharia also appear good in the form of islamic banking or non bank financial institutions in the form of sharia and one of these institutions is the Baitul Maal Wat Tamwil (BMT) from this background that emerges issues How is the legal position of treasury watamwil as financial and economic institutions in the community is not a bank and Any excess treasury wat tamwil compared with other financial institutions in the form of non bang sharia as for the method used in this paper is a normative research methods. Then after that lists several studies theories related to this problem include the theory of rule of law, justice theory and the theory of the enactment of Islamic law. later in the discussion presented on the definition of non bank financial institutions offensive sebahgian or some form of non-bank financial in the form of sharia among BMT coopertive sharia state its legal basis to determine the legal position of Islamic banks themselves in the discussion of the second half saw the advantages BMT itself compared with islamic financial institutions instead of another bank and it can be seen that the excess is other than in the form of financial management in the form of microeconomics is also engaged in social field with the aim to help the community (Ummah) who needs assistance such as charities or Called Amil zakat (CAZ) and other social activities and draw conclusions as the answer to the above problems